PENGARUH pH, LAMA PEMANASAN, SUHU PEMANASAN, KADAR GARAM DAN KADAR GULA TERHADAP STABILITAS EKSTRAK BUNGA BELIMBING WULUH (Averrhoa bilimbi L) - Haslina Haslina; Sri Budi Wahjuningsih (Badan Perencanaan Pembangunan, Penelitian dan Pengembangan Daerah Provinsi Jawa Tengah, 2014)
The aim of this research was to know on flower to ethanol ratio influence and the extraction time on starfruit flower extract. The research was also aimed to know pH, heating and temperature duration, salt and sugar levels effect at stability of starfruit flower extract. This research was conducted in two factorial randomized block design. The first factor was flower to ethanol ratio (1:1 b/v), (1:3 b/v) and (1:5 b/v) and the second factor was time extraction 40, 50 and 60 minute. Each treatment combination was conducted in triplication.The result of this research was analyzed using Anova, followed by 5 %. If it had interaction, it would be continued by DMRT 5% test. The result showed that on flower to ethanol ratio and time extraction influence significantly (p<0,05) on yield, pH, anthocyanin, colour intensity and vitamine C. Extract with on flower to ethanol ratio and time extraction as follows: yield of 26 %, pH of 3,91, anthocyanin content of 4,72 ppm and colour intensity of 22,35. Starfruit flower extract stable at 1-4, heating duration 70-80°C, temperature duration 0-90 minute, salt levels2-10% and sugar levels 10-50 %.